2012
DOI: 10.1177/1947603512444723
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of Exogenous Adenosine Triphosphate (ATP) for Cartilage Tissue Engineering

Abstract: Objective:While mechanical stimuli can be used to enhance the properties of engineered cartilage, a promising alternative may be to directly harness the underlying mechanotransduction pathways responsible. Our initial studies on the adenosine triphosphate (ATP)–purinergic receptor pathway demonstrated that stimulation by exogenous ATP improved tissue growth and properties but elicited matrix turnover under high doses (250 µM) potentially due to the accumulation of extracellular inorganic pyrophosphate (ePPi). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…Rosenthal et al reported that P2 receptor agonists, such as ATP and ADP, increased PPi production and accumulation in vitro; whereas suramin, a P2 receptor antagonist, suppressed this increase. Moreover, the cultures of bovine articular chondrocytes supplemented with 62.5–250 μM ATP increased biosynthesis and accumulation of matrix components and exhibited the improved tissue growth and properties (Waldman et al, ; Usprech et al, ). Chondrocyte pellet cultures treated with ATP produced more proteoglycans and collagen that enhanced their functional properties (Croucher et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Rosenthal et al reported that P2 receptor agonists, such as ATP and ADP, increased PPi production and accumulation in vitro; whereas suramin, a P2 receptor antagonist, suppressed this increase. Moreover, the cultures of bovine articular chondrocytes supplemented with 62.5–250 μM ATP increased biosynthesis and accumulation of matrix components and exhibited the improved tissue growth and properties (Waldman et al, ; Usprech et al, ). Chondrocyte pellet cultures treated with ATP produced more proteoglycans and collagen that enhanced their functional properties (Croucher et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Rosenthal, Hempel, Kurup, Masuda, and Ryan () confirmed that the P2 receptor agonists such as ATP and ADP increased pyrophosphate production and accumulation in chondrocytes cultured in vitro. Moreover, the cultures of bovine articular chondrocytes supplemented with 62.5–250 µM ATP increased the biosynthesis and accumulation of matrix components, leading ultimately to an improved tissue growth and enhanced functional biomechanical properties of cartilage (Usprech, Chu, Giardini‐Rosa, Martin, & Waldman, ). Another set of results reveals that ATP inhibited cartilage formation in micromass cultures of chick limb undifferentiated mesenchymal cells; however, they stimulated cartilage proteoglycan and collagen accumulation in bovine chondrocyte pellet cultures (for an extensive review see Burnstock et al, ).…”
Section: Differentiation Of Mscsmentioning
confidence: 99%
“…In the literature, the dose range of 62.5 – 125 µM ATP favored ECM production in articular chondrocytes in 3-dimensional agarose culture (Usprech, et al, 2012). Therefore, experimental groups included: Control (no ATP), 20 µM and 100 µM ATP treatment groups (NP: n = 9; AF: n = 9 for each group).…”
Section: Methodsmentioning
confidence: 99%